Analysis of Interpersonal Meaning Realized in Online News Texts of the Bali Times - J. Sutomo . (Dinamika Bahasa dan Budaya, 2015)
This study was conducted to portray some aspects of the contextual configuration of Bali Times’s news texts. The study focused on the analysis of interpersonal meaning of the selected news text genre. The method used is descriptive.Descriptive research provides a detailed profile of an event, condition or situation using either quantitative, qualitative or a combination of methods. Theapproaches are quantitative and qualitative approaches of discourse analysis to unfold the the role of interpersonal meaning in news text genre. The results revealed that the interpersonal meaning plays an important role in news text genre, and it may convey the authorial subjectivity of the writers. Key words: genre, news text genre, interpersonal meaning.